Doubles Game: Orko & Macić Versus Golem & Homunculus Igra parova: Orko i Macić protiv Golema i Homunculusa - Lozica, Ivan (Studia mythologica Slavica, 2011)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This short tennis analogy is the author’s attempt at revision and theoretical elaboration of the earlier paper on two imaginary beings of Croatian folklore. Broadening the scope and introducing comparison with similar literary characters and demons of learned culture might help us to better understand the contemporary role of belief narratives in remythologization processes within popular culture.